2014
DOI: 10.1017/s1368980014002390
|View full text |Cite
|
Sign up to set email alerts
|

The influence of early feeding practices on healthy diet variety score among pre-school children in four European birth cohorts

Abstract: Objective: The present study examined whether maternal diet and early infant feeding experiences relating to being breast-fed and complementary feeding influence the range of healthy foods consumed in later childhood. Design: Data from four European birth cohorts were studied. Healthy Plate Variety Score (HPVS) was calculated using FFQ. HPVS assesses the variety of healthy foods consumed within and across the five main food groups. The weighted numbers of servings consumed of each food group were summed; the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 32 publications
1
44
0
1
Order By: Relevance
“…CFg introduction (CFI) may influence infants' nutritional status and has short‐ and long‐term effects on health, especially regarding growth, obesity, and allergies (M. Fewtrell et al, ; A. D. Jones et al, ; Michaelsen, Larnkjaer, Lauritzen, & Molgaard, ; Michaelsen, Larnkjaer, & Molgaard, ; Moss & Yeaton, ; Onyango, Borghi, de Onis, Casanovas, & Garza, ; Pearce & Langley‐Evans, ), although the association between the timing of CFg and childhood obesity remains controversial (Burdette, Whitaker, Hall, & Daniels, ; Moorcroft, Marshall, & McCormick, ). CFg practices are also likely to influence later eating behaviour (L. Jones et al, ; Nicklaus, ; Schwartz, Scholtens, Lalanne, Weenen, & Nicklaus, ). CFI and its associated factors have been little studied in France to date (Betoko et al, ; Boudet‐Berquier, Salanave, de Launay, & Castetbon, ).…”
Section: Introductionmentioning
confidence: 99%
“…CFg introduction (CFI) may influence infants' nutritional status and has short‐ and long‐term effects on health, especially regarding growth, obesity, and allergies (M. Fewtrell et al, ; A. D. Jones et al, ; Michaelsen, Larnkjaer, Lauritzen, & Molgaard, ; Michaelsen, Larnkjaer, & Molgaard, ; Moss & Yeaton, ; Onyango, Borghi, de Onis, Casanovas, & Garza, ; Pearce & Langley‐Evans, ), although the association between the timing of CFg and childhood obesity remains controversial (Burdette, Whitaker, Hall, & Daniels, ; Moorcroft, Marshall, & McCormick, ). CFg practices are also likely to influence later eating behaviour (L. Jones et al, ; Nicklaus, ; Schwartz, Scholtens, Lalanne, Weenen, & Nicklaus, ). CFI and its associated factors have been little studied in France to date (Betoko et al, ; Boudet‐Berquier, Salanave, de Launay, & Castetbon, ).…”
Section: Introductionmentioning
confidence: 99%
“…This tendency to overlook diet is somewhat surprising, as research has found both breast-feeding (5,6) and dietary habits (13,14) to be associated with overweight/obesity. Even so, this small but growing body of research is quite consistent in its findings, suggesting that breast-feeding does indeed improve infant and child dietary patterns (7)(8)(9)(10)(11)(12) . This association appears to hold across multiple age groups and dietary components and may be partly explained by (i) lower maternal feeding restriction and enhanced infant self-regulation of intake (15) and/or (ii) repeated exposure of the breast-fed infant to the array of flavours found in the mother's diet that are transmitted through breast milk (11) .…”
mentioning
confidence: 83%
“…Despite the long line of literature linking breast-feeding to various health outcomes in offspring, only recently have scholars considered whether offspring dietary patterns during childhood are also predicted by breast-feeding history (7)(8)(9)(10)(11)(12) . This tendency to overlook diet is somewhat surprising, as research has found both breast-feeding (5,6) and dietary habits (13,14) to be associated with overweight/obesity.…”
mentioning
confidence: 99%
“…The results were similar when regressions were adjusted for maternal vegetable or fruit intake. Based on the analysis of data collected in EDEN, ALSPAC, and Generation XXI, it was also found that being breastfed for a short duration is associated with pre-school children eating a lower variety of healthy foods [5] ( Table 1 ). The results on timing of complementary feeding were not consistent across the cohorts.…”
Section: Early Feeding Practices and Eating Habits In Childhoodmentioning
confidence: 99%
“…Adapted from [5]. Results from generalized linear models between breastfeeding duration and Healthy Plate Variety score adjusted for age of introduction to fruit, age of introduction to vegetables, age of introduction to solid foods, child gender, maternal education level, maternal age and smoking during pregnancy.…”
Section: Learning To Eat Vegetables By Repeated Exposure and Role Modmentioning
confidence: 99%